Investigation of the association between serum protein concentrations and concurrent chronic kidney disease in hyperthyroid cats. (December 2017) - Williams, Tim L.; Elliott, Jonathan; Syme, Harriet M.; Archer, Joy
Abstract: Our objective was to identify if changes in serum protein concentrations occur in hyperthyroidism and to assess their association with the development of azotaemia following treatment. Initially non-azotaemic hyperthyroid cats and healthy older cats were included. Serum concentrations of protein fractions were determined by agarose gel electrophoresis and compared between; hyperthyroid and control cats, initially non-azotaemic hyperthyroid cats which developed azotaemia in a 4 month follow up period (masked-azotaemic) and those which remained non-azotaemic, and hyperthyroid cats before and at the time of restoration of euthyroidism. Data are presented as median [25th, 75th percentiles]. Hyperthyroid cats ( n  = 56) had higher serum α2 globulin concentrations (12.5 [10.9, 13.1] g/L vs. 9.8 [3.0, 11.4] g/L; P  < 0.001) and lower serum γ globulin concentrations (11.4 [9.1, 13.3] g/L vs. 14.0 [12.4, 16.8] g/L; P  = 0.001) than control cats ( n  = 26). Following treatment, serum total globulin concentration increased (from 38.6 [35.4, 42.8] g/L to 42.3 [39.0, 45.7] g/L; P  < 0.001), serum α2 globulin concentration decreased (from 12.5 [10.9, 13.9] g/L to 11.5 [10.1, 12.6] g/L; P  < 0.001) and serum γ globulin concentration increased (from 11.4 [9.0, 13.3] g/L to 14.0 [12.4, 16.8] g/L; P  < 0.001). Serum concentrations of total globulin or globulin fractions were not significantly different between masked-azotaemic and non azotaemic groups. In conclusion, hyperthyroidism is associated with altered serum concentrations of the α2 and γ globulin fractions, however these changes were not associated with the development of azotaemic chronic kidney disease following treatment. Highlights: Biomarkers of concurrent, but masked, azotaemic chronic kidney disease (CKD) in hyperthyroid cats are lacking. Hyperthyroid cats demonstrate mild changes in the serum alpha-2 and gamma globulins that resolve following treatment. Serum concentrations of all globulin fractions and total globulin are not associated with the development of azotaemia. Serum concentrations of globulin fractions and total globulin are not biomarkers of masked azotaemic CKD in hyperthyroidism.